Specific and individuated death reflection fosters identity integration - Blackie, Laura E.R.; Cozzolino, Philip, J.; Sedikides, Constantine (Public Library of Science, 2016)
Identity integration is the process wherein a person assimilates multiple or conflicting identities (e.g., beliefs, values, needs) into a coherent, unified self-concept. Three experiments examined whether contemplating mortality in a specific and individuated manner (i.e., via the death reflection manipulation) facilitated outcomes indicative of identity integration. Participants in the death reflection condition (vs. control conditions) considered positive and negative life experiences as equally important in shaping their current identity (Experiment 1), regarded self-serving values and other-serving values as equally important life principles (Experiment 2), and were equally motivated to pursue growth-oriented and security-oriented needs (Experiment 3). Death reflection motivates individuals to integrate conflicting aspects of their identity into a coherent self-concept. Given that identity integration is associated with higher well-being, the findings have implications for understanding the psychological benefits of existential contemplation.